Design and experimental study of piezoelectric energy harvester integrated in rotating vehicle tire using end-cap system - Muhammad Ikbal; Muhammad Rizal; Nurdin Ali; Teuku Edisah Putra (Results in Engineering)
Microsensors integrated into vehicle tires are becoming essential components in modern monitoring systems, enabling real-time detection as well as condition analysis to improve safety and efficiency. Therefore, this research aimed to design and develop a PVDF (Polyvinylidene Fluoride)-based piezoelectric energy harvester integrated into a vehicle tire using a TPU (thermoplastic polyurethane) end-cap system resistant to high deformation and extreme heat. The harvester was designed to convert mechanical energy into electrical from tire deformation during rotation, enabling the operation of wireless sensors. This research also evaluated the effects of tire load and rotation speed variations on the harvester performance. The experimental results showed that the maximum instantaneous output voltage ranged from 41 to 63 V, with a maximum power in a parallel configuration of 0.203 mW Root Mean Square (RMS) and 3.42 mW (peak), as well as a high power density of 3.11 μW/mm³. Additionally, the system was capable of charging a 22 µF capacitor to a saturation voltage of 14 V. The use of TPU material for the end-cap ensured resistance to deformation and high temperatures, making the device reliable and efficient in harvesting mechanical energy in harsh environments. The results showed that the proposed harvester design could efficiently convert mechanical energy into electrical with significant potential to support wireless sensors integrated into vehicle tires, offering a sustainable and reliable solution in vehicle monitoring systems.